2018
DOI: 10.21315/tlsr2018.29.2.13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cultivable Bacteria from Tropical Marine Sponges and Their Biotechnological Potentials

Abstract: Marine sponges are acknowledged as bacterial hotspots in the oceanic biome. Aquatic bacteria are being investigated comprehensively for bioactive complexes and secondary metabolites. Cultivable bacteria associated with different species of sea sponges in South China Sea waters adjacent to Bidong Island, Terengganu were identified. Molecular identification was accomplished using 16S rRNA gene cloning and sequencing. Fourteen bacterial species were identified and their phylogenetic relationships were analysed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…By applying a culture-dependent approach, we successfully isolated 151 strains from the sponge Ophlitaspongia sp., as well as their representative strains, which are distributed across 20 genera from 18 families in 4 phyla and include Actinobacteria , Bacteroidetes , Firmicutes , and Proteobacteria . Phylogenetic analyses confirmed that all 20 genera of the isolated strains overlapped with previously reported isolates associated with sponges and other marine hosts, such as corals, ascidians, and algae, from different geographical locations obtained using culture-dependent methods [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Genera such as Bacillus , Microbacterium , Nocardiopsis , Pseudoalteromonas , Saccharomonospora , and Streptomyces are distributed throughout aquatic environments and are well-known secondary metabolite producers that may protect host sponges from microbial infection and predators [ 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 80%
“…By applying a culture-dependent approach, we successfully isolated 151 strains from the sponge Ophlitaspongia sp., as well as their representative strains, which are distributed across 20 genera from 18 families in 4 phyla and include Actinobacteria , Bacteroidetes , Firmicutes , and Proteobacteria . Phylogenetic analyses confirmed that all 20 genera of the isolated strains overlapped with previously reported isolates associated with sponges and other marine hosts, such as corals, ascidians, and algae, from different geographical locations obtained using culture-dependent methods [ 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. Genera such as Bacillus , Microbacterium , Nocardiopsis , Pseudoalteromonas , Saccharomonospora , and Streptomyces are distributed throughout aquatic environments and are well-known secondary metabolite producers that may protect host sponges from microbial infection and predators [ 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Discussionsupporting
confidence: 80%
“…The analysis of the microbial composition of a sample can be performed using high-throughput sequencing methods by amplifying and sequencing selected regions of a gene (a metagenetic approach) or whole metagenomic DNA. Amplicon sequencing of regions such as the 16S ribosomal RNA gene (16S rRNA) continue to provide a simplified approach that is widely applied for bacterial identification and microbial community profiling [1][2][3] even though there are newer approaches which involve sequencing of whole metagenomes. This is in part due to being an order of magnitude cheaper compared to a shotgun metagenomic approach while also being able to cope with the presence of a high background of contaminating (e.g.…”
mentioning
confidence: 99%
“…These include rare Actinomycetes (Tioman island) [6]; polysaccharides producing Theonella sp. (Bidong island) [7]; pigmented bacterium (Tinggi Island) [8]; several cultivable bacterium (Bidong Island) [9]; and Streptomyces (Andaman sea) [10]; haloalkanoic acid degrading Bacillus aryabhattai [11]; and moderately halophilic lipase producing bacterium (Pahang coast) [12]. The potential of sponge associated microbes in bioprospecting of bioactive compound have been described [13], [14].…”
Section: Introductionmentioning
confidence: 99%